Pendidikan Komunikasi Islam di Tengah Konvergensi Media - Abrar, Ana Nadhya (Jurnal Komunikasi Islam, 2013)
This paper will exlore how Islamic universities take advantages from the dynamics of the mass media that undertake the media convergence due to the demands of information technology and communications develop–ment. As a conclusion, the paper argues that Departements of Communication or Islamic Communication and Broad–cast need to pay more attention to the technical opera–tions orientation of thelearning system. This, at the end, will also offer great employment opportunities for the graduates as well as the propagation of Islam.Keywords: communication education, technical orien–tation, media convergence, online journalism------------------------------------------------------------------------------Tulisan ini mengulas bagaimana perguruan tinggi Islam memanfaatkan peluang dari dinamika media massa yang sudah melakukan konvergensi akibat tuntutan kema–juan teknologi informasi dan komunikasi. Artikel ini ber–pendapat bahwa jurusan ilmu komunikasi atau komunikasi dan penyiaran Islam perlu lebih memperhatikan orientasi operasi teknis dalam sistem pembelajarannya, yang menawarkan peluang besar bagi lapangan kerja sekaligus dakwah Islam.Kata Kunci: pendidikan komunikasi, orientasi teknis, konvergensi media, jurnalisme online.